2019
DOI: 10.1016/j.ijid.2018.11.251
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about influenza and compliance with the recommendations for influenza vaccination of pregnant women in Greece

Abstract: Purpose: Avian influenza A(H7N9) is considered an important zoonotic pathogen, human cases of which have been increasing in multiple epidemics waves since it was idnetified in 2013. Characterising the temporal pattern of mortality or clinical severity of human infection can identify changes in viral pathogenicity and help inform emergence and pandemic risk assessments. Here, we consider how the severity of A(H7N9) in humans has changed by epidemic wave, after adjusting for demographic and spatial factors, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, education of HCPs alone is unlikely to be sufficient, as parental vaccine hesitancy also needs to be addressed through specific public awareness campaigns (Healy et al, 2015). The impact of education on vaccination uptake is exemplified by an educational intervention at a large maternity hospital in Greece, where education resulted in an increase in antenatal influenza vaccination rate from below 2% to 20% (Maltezou et al, 2019). Furthermore, a study from Brazil found that maternal acceptance of influenza vaccination in pregnancy improved following a government campaign and HCP endorsements during prenatal visits.…”
Section: Education On the Benefits Of Antenatal Vaccination Influences Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…However, education of HCPs alone is unlikely to be sufficient, as parental vaccine hesitancy also needs to be addressed through specific public awareness campaigns (Healy et al, 2015). The impact of education on vaccination uptake is exemplified by an educational intervention at a large maternity hospital in Greece, where education resulted in an increase in antenatal influenza vaccination rate from below 2% to 20% (Maltezou et al, 2019). Furthermore, a study from Brazil found that maternal acceptance of influenza vaccination in pregnancy improved following a government campaign and HCP endorsements during prenatal visits.…”
Section: Education On the Benefits Of Antenatal Vaccination Influences Uptakementioning
confidence: 99%
“…HCPs recommend vaccination to pregnant women (Wiley et al, 2013;Wilson et al, 2015) Enabling of HCPs through training, reimbursement, and management of workload (Wilson et al, 2015) Pregnant women having face-to-face consultations with HCPs (McCarthy et al, 2015) Internet and text messaging as information sources about influenza vaccination (McCarthy et al, 2015) Education on benefits of antenatal influenza vaccination Improved awareness of maternal immunisation among HCPs who do not traditionally administer vaccinations (Healy et al, 2015;Maltezou et al, 2019) Prenatal vaccine education of expectant mothers (Kfouri Rde and Richtmann, 2013;O'Leary et al, 2019;Vojtek et al, 2018)…”
Section: Regulatory Processesmentioning
confidence: 99%
“…[15][16][17] Nevertheless, vaccination rate of this vulnerable population is low. 15 Additionally, although immunisation of pregnant women against influenza has been recommended according to GNIP since 2008, 18 we recorded seven influenza cases in young infants in 2016-2017 and 2019 which might have been prevented by maternal immunisation. In accordance with our findings, a recent study has shown that knowledge and uptake of influenza vaccine among pregnant women in Greece are poor.…”
Section: Discussionmentioning
confidence: 84%